STRATEGIES AND RESOURCES APPLIED TO LUDIC ACTIVITIES FOR AUTONOMY AND INDEPENDENCY ACQUISITION OF BLIND AND LOW VISON CHILDREN. (Fiep Bulletin - online, 2012)
The present research aims to identify strategies and adapted pedagogic resources to favor the intervention of physical activity teacher that acts with special and inclusive education, in order to ensure more independency, autonomy and social inclusion to the disable person. The procedure includes evaluation, construction and/or adaptation of strategies and pedagogic resources necessary to the limitations and capacities of different disable groups that will be assisted by motor, ludic and recreational activities based on Siaulys method (2008). The project is developed in the Philanthropic Association for the Protection of Blind People of Presidente Prudente, which provides educational, therapeutic and technical formation work to their participants.
Keywords: Visually impaired persons; psychomotor performance; adapted resources